2021
DOI: 10.1055/s-0041-1731678
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nonproprietary Measures of Ambulatory Electronic Health Record Use Associated with Physician Work Exhaustion

Abstract: Background Accumulating evidence indicates an association between physician electronic health record (EHR) use after work hours and occupational distress including burnout. These studies are based on either physician perception of time spent in EHR through surveys which may be prone to bias or by utilizing vendor-defined EHR use measures which often rely on proprietary algorithms that may not take into account variation in physician's schedules which may underestimate time spent on the EHR outside of scheduled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Most studies were observational (91 articles) while a minority were experimental (11 articles). Nine of the observational studies examined associations between EHR use and an outcome in the cohort of observed users such as burnout, 6 , 7 , 33 , 46 , 47 , 67 , 69 turnover, 28 and stress. 71 Three observational studies examined associations between EHR use and clinical outcomes including next-day discharge, 78 length of stay, 84 and speed of consult response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were observational (91 articles) while a minority were experimental (11 articles). Nine of the observational studies examined associations between EHR use and an outcome in the cohort of observed users such as burnout, 6 , 7 , 33 , 46 , 47 , 67 , 69 turnover, 28 and stress. 71 Three observational studies examined associations between EHR use and clinical outcomes including next-day discharge, 78 length of stay, 84 and speed of consult response.…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 6 , 19 , 25 , 27 , 29 , 32 , 34 , 36 , 39 , 40 , 42 , 48 , 49 , 51 , 53 , 55 , 66 , 69–71 An overlapping set of 22 articles, including 9 that also reported time period-based measures, reported at least 1 measure based on clinician schedules. 4 , 6 , 19 , 27 , 28 , 30 , 34 , 37 , 38 , 40 , 41 , 43 , 44 , 47–50 , 67 , 69 , 72 , 77 , 119 These included time outside scheduled hours on days with appointments, time on days without appointments, and time after the patient checked out. These schedule-based measures differed in whether they (1) measured active EHR use or all time logged into the EHR, (2) included mid-day meetings or breaks in scheduled hours, or (3) included the 30 or 60 min before and after the first and last appointment of the day in scheduled hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The comprehensive adoption of electronic health records (EHRs) has triggered many unintended consequences, including those contributing to physician burnout. [3][4][5][6][7][8][9][10] A study conducted with 1,800 physicians from Rhode Island found that burnout prevalence was considerably higher among physicians who used EHRs, with 27.2% of the group reporting one or more burnout symptoms, compared with 13.6% of physicians who did not use EHRs. 2,11 Another study showed that spending more than 6 hours per week on afterhours EHR work was strongly associated with the perception that EHR use affects both work-life balance and burnout.…”
mentioning
confidence: 99%
“…2,11 Another study showed that spending more than 6 hours per week on afterhours EHR work was strongly associated with the perception that EHR use affects both work-life balance and burnout. 12 Sinha et al showed how EHR use correlates with physician exhaustion, 9 Marmor et al showed how time spent on EHR use during the day had an inverse relationship with patient satisfaction scores, 13 and Frintner et al showed how EHR use by pediatricians was associated with worse work-life balance, stress in balancing responsibilities, and less career and life satisfaction. 14 Studies have also shown differences between male and female clinicians on various factors associated with EHR use, including stress, frustration, and burnout rates.…”
mentioning
confidence: 99%